Effectiveness of Morelet's crocodile as a bioindicator of metal pollution and metallothionein response to spatial variations of metal exposure - A.M. Buenfil-Rojas; T. Alvarez-Legorreta; M. González-Jáuregui; J. Rendón-von Osten; J.R. Cedeño-Vázquez (Environmental Advances, 2022)
Several studies have assessed the potential of crocodylians as bioindicators of environmental contamination. In this study, the Morelet's crocodile (Crocodylus moreletii) was used as a bioindicator of metal pollution across five locations in southeastern Mexico classified as having high, medium, and low anthropogenic impact. Total length and sex were determined for each animal and concentrations of metals and metallothioneins (MTs) were determined by using non-destructive tissues. Mercury (Hg) concentrations in crocodile blood and scutes generally exhibited a decreasing pattern from the higher impacted site to the lower impacted site (x2(14) = 185.42, p < 0.001), suggesting that concentrations in these samples are sensitive enough to identify difference in the bioavailability of Hg within crocodile populations. The highest concentrations were detected in scutes from Laguna Guerrero (Hg = 0.60 ± 0.217 µg/g w.w.) and Nichupté-Bojorquez (Cd = 14.99 ± 2.95 µg/g w.w., Cu = 58.66 ± 11.29 µg/g w.w., Zn = 80.86 ± 80.54 µg/g w.w.). MTs in blood plasma were detected at all sites (27.48 ± 4.78 µg/mL) but was low in erythrocytes detection frequency, suggesting this latter fraction may not be useful for MTs analysis. In general, our study supports the utility of crocodiles as bioindicators of xenobiotic metal pollution. However, it is necessary for such studies to perform assays for specific MT isoforms and the effective concentrations of metals bound to this protein, and to determine metal concentrations in multiple environmental matrices from the sites under evaluation.